Multiple Quantum Coherences Hyperpolarized at Ultra‐Low Fields. Issue 21 (17th October 2019) - Buckenmaier, Kai; Scheffler, Klaus; Plaumann, Markus; Fehling, Paul; Bernarding, Johannes; Rudolph, Matthias; Back, Christoph; Koelle, Dieter; Kleiner, Reinhold; Hövener, Jan‐Bernd; Pravdivtsev, Andrey N.
Abstract: The development of hyperpolarization technologies enabled several yet exotic NMR applications at low and ultra‐low fields (ULF), where without hyperpolarization even the detection of a signal from analytes is a challenge. Herein, we present a method for the simultaneous excitation and observation of homo‐ and heteronuclear multiple quantum coherences (from zero up to the third‐order), which give an additional degree of freedom for ULF NMR experiments, where the chemical shift variation is negligible. The approach is based on heteronuclear correlated spectroscopy (COSY); its combination with a phase‐cycling scheme allows the selective observation of multiple quantum coherences of different orders. The nonequilibrium spin state and multiple spin orders are generated by signal amplification by reversible exchange (SABRE) and detected at ULF with a superconducting quantum interference device (SQUID)‐based NMR system. Abstract : Ultra‐low field COrrelation SpectroscopY (ULF COSY) : Hyperpolarized homo‐ and heteronuclear ( 1 H‐ 19 F) multiple quantum coherences (MQCs) from zero to the third order were observed at 91 μT by SQUID based NMR. MQCs were assigned by using density matrix simulations and measured here by a phase cycling modified ULF COSY sequence. The method allowed us to look deeper inside hyperpolarization processes at low magnetic fields.